2016
DOI: 10.4103/0972-124x.175173
|View full text |Cite
|
Sign up to set email alerts
|

The relation of gingival thickness to dynamics of gingival margin position pre- and post-surgically

Abstract: Background:To evaluate the gingival margin position (GMP) before and after open flap debridement in different gingival thickness (GT).Materials and Methods:Twenty-seven healthy patients with moderate to advanced adult periodontitis were included in a randomized control clinical trial. A calibrated UNC-15 periodontal probe, an occlusal onlay stent was used for clinical measurements recorded at baseline, 3 month, 6 month, and 16 month. The changes in the GMP were studied at midbuccal (Mi-B), mesiobuccal (MB), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Differences in bREC change between groups as observed in thin and thick gingival tissues (Table 5) seem to suggest the beneficial effect of the CTG may partially reside in the increase in gingival thickness. Consistently, previous studies have shown that thick gingival tissues exhibit a greater resistance to recession due to surgical trauma and tissue remodeling after different surgical procedures, including regenerative surgery 31–34 . It may also be speculated that conversion from a thin to a thick phenotype may have a beneficial effect on long‐term stability of the gingival profile, since thick biotypes have been shown to be less prone to developing gingival recessions 35 …”
Section: Discussionmentioning
confidence: 59%
“…Differences in bREC change between groups as observed in thin and thick gingival tissues (Table 5) seem to suggest the beneficial effect of the CTG may partially reside in the increase in gingival thickness. Consistently, previous studies have shown that thick gingival tissues exhibit a greater resistance to recession due to surgical trauma and tissue remodeling after different surgical procedures, including regenerative surgery 31–34 . It may also be speculated that conversion from a thin to a thick phenotype may have a beneficial effect on long‐term stability of the gingival profile, since thick biotypes have been shown to be less prone to developing gingival recessions 35 …”
Section: Discussionmentioning
confidence: 59%
“…The GT has an influence on the postoperative position on GMP i.e., thicker gingiva of more than 1 mm showed minimal recession. [13] The pocket depth reduction was statistically significant within A-PDLSc Ni group and OFD group, but on comparison between the groups A-PDLSc Ni group showed significant PPD reduction of 27%, 33%, and 34% at 6, 9, and 12 months, respectively. There was a significant improvement in CAL in OFD group at 9 months and 12 months, but A-PDLSc Ni showed significant CAL improvement which was 38%, 44%, and 45% at 6, 9, and 12 months than OFD group.…”
Section: Discussionmentioning
confidence: 95%
“…The gingival margin tissue 26 of natural tooth and mucosal margin tissue 33 has a tendency to recede due to bone loss. Therefore, they both are not useful as dependable measurements to appreciate changes from baseline to postoperatively.…”
Section: Limitations O F Probing Pocket Depth a N D Peri-implant Probing Depthmentioning
confidence: 99%
“…• Gingival margin 26 • Mucosal marginal position • Cement-enamel junction • As CEJ is missing, fixed reference point on implant (e.g., implant shoulder for 1 stage nonsubmerge implant) or its suprastructure • Base of the sulcus/pocket…”
Section: Landmarksmentioning
confidence: 99%